THE DESIGN OF INTEGRATED SOLID WASTE MANAGEMENT SITE (TPST) IN BANGUNTAPAN DISTRICT, BANTUL REGENCY - Hasbi Ash Shiddiq, Rifki
The increase in population will affect the production of waste generated in each city/regency which is then accommodated in the TPST. In addition, the limitations of adequate management facilities at the source make waste management problems even more complex. In Banguntapan District, which consists of 8 villages with a population of 115,127 people, there are only three facilities TPS 3R or Waste Management Sites with the 3R principles (reduce, reuse, and recycle). This causes waste to be transported to the Final Processing Site (TPA) without going through reduction from the source. For this reason, it is necessary to design an Integrated Waste Processing Facility (TPST) to maximize the reduction rate at the source. The design is carried out by first sampling the waste generation in Banguntapan District. The waste that is obtained is then calculated as a percentage of its composition and analyzed for its waste characteristics. The sampling data is used as the basis for initial consideration in determining the technology and further used for the design of the infrastructure to be built. Technology determination is carried out using the Analytic Hierarchy Process (AHP) method. The organic waste treatment technologies used are vermi composting, combination Black Soldier Fly (BSF) with windrow composting, in-vessel composting, and anaerobic digester. Then, the mixed waste processing technologies used are Refuse Derived Fuel (RDF), incineration, gasification, and pyrolysis. Based on the weighting results with the AHP method, the technology for processing organic waste by Black Soldier Fly (BSF) in combination with windrow composting method has been selected, while for mixed waste, the technology for making Refuse Derived Fuel (RDF) has been selected. The TPST design will be built in an area of 8,000 m2 by utilizing the vacant land available in Potorono Village. From the CAPEX calculation, it is found that the construction of the TPST will require funds of Rp 31.459.357.000. Meanwhile, the results of the OPEX calculation found that for one year at least Rp 5,525,403,000 is needed.